Influence of habitat heterogeneity on avian diversity in the Rajparian Wildlife Sanctuary, Kashmir Himalaya - Aadil Hussain Bhat; Altaf Hussain Mir; Samina Amin Charoo (Journal of Basic and Applied Zoology, 2023)
Abstract Background The value of local and regional landscapes for avian conservation requires a thorough understanding of the diversity and structure of bird communities. Avifauna serves as an important biological indicator in monitoring the health of an ecosystem or environment. The present study was conducted to examine the relationship between avian diversity, richness, composition and habitat characteristics at the Rajparian Wildlife Sanctuary. Results Using geographic information systems and remote sensing techniques, we analyzed habitat heterogeneity based on land use and land cover classification. For sampling birds, extensive surveys were conducted in different land-use types from 2019 to 2021, following the line transect method. During the study period, 102 bird species were recorded from the five studied vegetation types of the study area, including one near threatened (Bearded Vulture) and one vulnerable (Kashmir Flycatcher) bird species. The highest numbers of avian species were recorded from the forest (71 species) (42.61 ± 16; mean ± SD) and the lowest from the rocky land-use type (12 species) (7.83 ± 1.95). The individual rarefaction and extrapolation curves showed higher species richness for forest and the lowest for rocky habitats. Numerous pairwise comparisons revealed significant differences in species richness among studied habitat types, except for riverine vs. grassland, scrub vs. grassland and rocky vs. riverine land uses. The partitioning of the spatio-temporal β-diversity patterns revealed a relatively large contribution of the turnover component to the observed overall dissimilarity compared to the nestedness component. Conclusions It can be concluded that avian communities in the Rajparian Wildlife Sanctuary are influenced by habitat heterogeneity, topography, and the availability of water. The results of the present study indicate that the Rajparian Wildlife Sanctuary provides an important habitat for the conservation of birds, as it harbors a rich avian diversity. The study is the first scientific survey of the avian habitat associations in the protected area and will serve as a baseline for future avian research, as well as for management implications in the region.